Exploring university students’ preferences and satisfaction in utilizing digital tools for foreign language learning - Pikhart, Marcel; Klimova, Blanka; Al-Obaydi, Liqaa Habeb (Frontiers in Education, 2024)
This article investigates the utilization of digital resources, including applications like Duolingo, ChatGPT, and Google Translate, in the language learning practices of English as a Foreign Language (EFL) college students from the Czech Republic, Taiwan, and Iraq. Through a questionnaire-based approach, the study explores the digital tools employed, activities conducted, satisfaction levels, and the impact on language skills. Findings reveal diverse usage patterns and positive perceptions, highlighting the multifaceted role of digital resources in vocabulary acquisition, skill development, and language exploration. While participants express overall satisfaction, challenges such as connectivity issues and content variety are identified. The study's most important finding is that digital resources like Duolingo, ChatGPT, and Google Translate significantly enhance EFL students' language learning experiences through increased engagement and skill development, despite challenges such as connectivity issues and content diversity. The study underscores the need for ongoing improvement in digital language learning tools and suggests avenues for future research, emphasizing long-term impact, personalized learning paths, emerging technologies, and socio-emotional aspects. Despite limitations, the research provides valuable insights into the dynamic interplay between technology and language education in diverse cultural contexts.